2011
DOI: 10.3892/ijo.2011.936
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis using long-term preserved formalin-fixed and paraffin-embedded tissue of non-small cell lung cancer

Abstract: Abstract. This study was performed to evaluate RNA extraction and gene expression analysis of non-small cell lung cancer (NSCLC) using formalin-fixed and paraffin-embedded (FFPE) specimens stored for more than 20 years by quantitative PCR (qPCR) and DNA microarrays. Long-term preserved FFPE materials enable large retrospective studies correlating molecular features with therapeutic response and clinical outcome. qPCR was used to evaluate RNA extraction methods and to compare DNA microarray gene expression prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Some of the dysregulated genes could serve as good candidate for biomarkers or targets for seizure management. Our analyses also validate the notion that meaningful genomic data can be acquired from a widely available and valuable clinical resource [15][27].…”
Section: Introductionsupporting
confidence: 73%
“…Some of the dysregulated genes could serve as good candidate for biomarkers or targets for seizure management. Our analyses also validate the notion that meaningful genomic data can be acquired from a widely available and valuable clinical resource [15][27].…”
Section: Introductionsupporting
confidence: 73%
“…7, 48 qPCR has been used to obtain gene expression data from FFPE samples from different tissue types and organs, often with tumor specimens to improve prognostic accuracy in clinical care. 7, 12, 15, 49 For example, RNA from FFPE samples of 153 breast cancer patients were used to develop an 8-gene qPCR gene expression score of prognostic value that could be reasonably implemented in clinical settings without the need for fresh frozen RNA or more costly commercial signature arrays. 7 One recent study identified a 14 gene expression signature using qPCR with FFPE RNA from a 361 patient cohort to predict survival in nonsquamous, non-small-cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…4, 11, 12 Although less comprehensive than microarray platforms, quantitative PCR (qPCR) is considered one of the most sensitive methods for comparing a wide range of gene expression levels, it is frequently used to confirm signatures generated by microarray platforms and it is reliable even when the RNA is of low amount and quality. 13 qPCR of RNA extracted from clinical FFPE samples is being used to detect the presence of gene signatures in an effort to improve patient diagnosis and to predict therapeutic response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FFPE tissue specimens are thought to be unsuitable for genetic examination after long periods of time have elapsed. However, molecular biological technologies for examining archival FFPE samples are now more developed [2, 9, 10, 12, 14, 29, 32, 34]. The possibility of measuring mRNA levels in FFPE tissue specimens has been reported, despite RNA fragmentation [6, 9, 10, 27, 29, 31, 34].…”
Section: Introductionmentioning
confidence: 99%